خوارزمية القائمة السوداء الديناميكية للحماية من هجوم حجب الخدمة الموزع DDoS في شبكة العربات المتنقلة - بشرى معلا; علاء محفوض (Tishreen University, 2018)
شبكات العربات المتنقلة هي مجموعة من العربات التي تحتوي على تجهيزات خاصة تمكنها من الاتصال فيما بينها مشكلة شبكة لاسلكية. تعد الهجومات على الشبكة من أخطر التحديات التي تواجه هذه الشبكات، لا سيما تلك التي تستهدف متطلب التوافرية، الذي يعد من أهم متطلبات الأمن في شبكات VANET . من أهم هذه الهجومات هجوما حجب الخدمة DoS وحجب الخدمة الموزع DDoS لأنهما يجعلان الشبكة غير متاحة للمستخدمين الفعليين فيها. نقدم فـي هذا الـبحث اقتراحاً لخوارزمية كشف هجوم DDoS والتصدي له عند حدوثه. تعتمد هذه الخوارزمية على قائمة سوداء تتضمن معرف العربات الخبيثة التي يتم اختيارها بناءً على قيمة عتبة معينة لعدد الرسائل المستقبلة منها. ونقدم تحليلاً لأداء هذه الخوارزمية بالاعتماد على بارامترات الإنتاجية ومعدل وصول الرزم والتأخير نهاية إلى نهاية ومقارنتها مع أداء خوارزمية QLA.لتحقيق هذا الغرض استخدمنا المحاكي NS 2.35 مع استخدام إضافاتلدعم اتصالات العربات المتنقلة (WAVE).وقد بينت نتائج المحاكاة أن الخوارزمية المقترحة تخفض تأثير الهجوم بشكل ملحوظ إذ تزيد من الإنتاجية ومعدل الرزم المستلمة. A Vehicular Ad-hoc Network (VANET) is a group of vehicles, which have special equipments enable them to connect with each other as a wireless network .The attacks are considered as the most serious challenge against this network, especially those targeting   availability requirement, which is one of the most important security requirements in VANET. The Denial of Service (DoS) and Distributed Denial of Service (DDoS) attacks are the most important attacks since they make the network not available for actual users. In this research, we present an algorithm to detect and face the DDoS attack. This algorithm depends on a black list contains the IDs for malicious vehicles, which are being chosen depending on a certain threshold value for a number of messages received from them. We analyze the algorithm performance depending on throughput, packet delivery ratio, end to end delay parameters, and compare it with the performance of the Queue Limiting Algorithm (QLA) .To achieve this purpose, we use NS2.35 simulator using details to support Wireless Access in Vehicular Environments (WAVE). The simulation results showed that the proposed algorithm reduces the effect of the attack Significantly since it increases the throughput and packet delivery ratio.